Hematopoietic stem cell transplantation in children with Griscelli Syndrome type 2: Experience and outcomes - Devika Gupta; Deepshi Thakral; Sameer Bakhshi; Sushil Kumar Kabra; Dipendra Kumar Mitra (Wolters Kluwer Medknow Publications, 2019)
Griscelli syndrome is a rare autosomal recessive inherited disorder characterized by hypopigmentation, silver colored hair, and associated immunological deficiency, which proves fatal in the absence of timely intervention. Our patients diagnosed with Griscelli syndrome-2 presented with fever, hepatosplenomegaly, and deranged hematological and biochemical parameters. Both cases underwent detailed investigations comprising of hair mount microscopic examination, degranulation assay, and mutational studies. Our cases showed defective degranulation activity by NK cells and gene mutation analysis revealed RAB27A mutation that causes defect of cytotoxic granule exocytosis from natural killer (NK) and T-cells, manifesting clinically as hemophagocytic lymphohistiocytosis (HLH). Hematopoietic stem cell transplantation in one of the patients resulted in stable chimerism; however, the second case relapsed within a month after SCT. Stem cell transplantation is the only curative therapeutic option for GS2; thus, improvement in posttransplantation management may reduce mortality and posttransplant complications. Hence, any child who presents with partial albinism and clinical features suggestive of HLH, a peripheral blood, hair shaft mount examination along with basic immunological NK and T-cell cytotoxicity assay by flow cytometry will help clinch the diagnosis early. It can subsequently be confirmed by molecular study. Timely therapeutic intervention can prevent relapses and severe infection and improve outcome in these cases.